Designing an Illustrated Book About Kupang as the Identity of Sidoarjo - Ruliawan, Tsania Rahma; Aji, Restu Ismoyo; Arifianto, Pungky Febi (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2025)
This writing discusses the design of an illustrated book about kupang, a traditional culinary dish from Sidoarjo that is still relatively unknown. Lontong kupang is often considered part of Surabaya's cuisine, but kupang holds significant cultural and historical value for the people of Sidoarjo. The purpose of this illustrated book is to raise awareness and appreciation for kupang, while also strengthening Sidoarjo’s culinary identity beyond the more popular bandeng and shrimp. Through direct observation in Balongdowo, a kupang processing center, the study examines the processes of harvesting, separating the meat, and processing kupang into petis, crackers, and lontong. Additionally, interviews with industry players provide deeper insights. The findings are presented as engaging stories that illustrate the role of kupang in community life, using watercolor techniques and digital media to highlight kupang as a culturally rich element.